1921
DOI: 10.1002/prac.19211020801
|View full text |Cite
|
Sign up to set email alerts
|

Über arylierte Pyridine und ihre Beziehungen zu den entsprechenden Pyryliumverbindungen. II

Abstract: Wahrend die aliphatischen Abkommlinge des Pyridins in groBer Mannigfaltigkeit bekannt und untersucht sind, ist dies bei den rein aromatischen Vertretern, insbesondere denjenigen, deren Phenylreste Substituenten tragen, nicht der Fall. Das hat seinen Grund darin, daB die Methoden, welche leicht zu aliphatischen Aminen fuhren, in der aromatischen Reihe entweder ganz versagen oder nur geringe Ausbeuten liefern. Als sich nun der von Baeyer und P i c c a r d 2) an aliphatischen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Owing to their wide range of pharmacological activity and industrial and synthesis applications, a number of methods have been reported for the synthesis of Kröhnke‐type pyridines [7]. Previously, 2,4,6‐triarylpyridines have been prepared by the condensation of 1,5‐diketones with formamide‐formic acid [8] and by other synthetic procedures including the Chichibabin method [9–12]. Following this procedure, the yields of single products are low because of the formation of mixtures of pyridines and various by‐products [12].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their wide range of pharmacological activity and industrial and synthesis applications, a number of methods have been reported for the synthesis of Kröhnke‐type pyridines [7]. Previously, 2,4,6‐triarylpyridines have been prepared by the condensation of 1,5‐diketones with formamide‐formic acid [8] and by other synthetic procedures including the Chichibabin method [9–12]. Following this procedure, the yields of single products are low because of the formation of mixtures of pyridines and various by‐products [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their importance from a pharmacological and synthetic point of view, comparatively few methods for the preparation of 2,4,6-triarylpyridines (commonly named as Krohnke pyridines) have been reported in the literature. [4][5][6][7][8][9] New amongst these methods is the cyclo-condensation reaction of acetophenones, benzaldehydes and NH 4 OAc using conventional heating in the presence of Brønsted and Lewis acid catalysts. [10][11][12][13] The overall aim of this study was to develop and validate an efficient protocol for the synthesis and easy purification of 2,4,6-triarylpyridines from the cyclo-condensation reaction of acetophenones, benzaldehydes and NH 4 OAc in the presence of BaCl 2 -nano SiO 2 as an efficient catalyst (Scheme 1).…”
mentioning
confidence: 99%